Investigating the Hull Girder Strength of the MST-3 Vessel Using Finite Element Analysis (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Ship longitudinal strength analysis is critical for ensuring structural integrity and safety throughout the vessel's operational life. This study presents a comprehensive finite element analysis (FEA) of the MST-3 vessel's longitudinal strength using ANSYS software, focusing on hull girder behaviour under extreme loading conditions. The research employed advanced computational methods to evaluate structural response under sagging and hogging conditions, incorporating material nonlinearity, initial imperfections, and residual stresses from welding processes. The MST-3 vessel, with principal dimensions of 185.0m LOA, 28.5m beam, and 15.2m depth, was modelled using 68,530 finite elements (SHELL181 and BEAM188) with 72,840 nodes. The analysis incorporated AH36 steel material properties with yield strength of 355 MPa and considered initial deflections following elastic buckling modes. Boundary conditions were applied using multi-point constraints (MPC) at the model extremities to simulate simply supported conditions. Results demonstrate that the vessel meets all classification rule requirements with significant safety margins. The ultimate bending moment capacity reached 1,245,680 kN⋅m under sagging conditions and 1,187,420 kN⋅m under hogging conditions, exceeding design requirements by 39.1%. Maximum von Mises stress of 284.7 MPa occurred at hatch corner connections, representing 80.2% of yield strength. Critical stress concentrations were identified at deck-side shell junctions (267.3 MPa), engine room bulkheads (245.8 MPa), and cargo hold corners (231.5 MPa). The progressive collapse analysis revealed ductile failure behaviour with adequate post-ultimate strength reserves. Buckling analysis showed minimum safety factors of 1.85 for all structural components, with longitudinal girders exhibiting the lowest buckling margins. The finite element methodology demonstrated excellent correlation with analytical beam theory solutions, validating the computational approach with maximum differences below 1%. Key findings indicate that while the vessel structure is adequate, hatch corner reinforcement is recommended to address stress concentrations. The study concludes that modern finite element techniques provide reliable tools for ship structural assessment when properly validated. The developed methodology offers practical engineering solutions for longitudinal strength evaluation and optimization of marine structures.